2020
DOI: 10.3389/fmicb.2020.569019
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Trends in Biological Treatment of Wastewater From Unconventional Oil and Gas Extraction

Abstract: Unconventional oil and gas exploration generates an enormous quantity of wastewater, commonly referred to as flowback and produced water (FPW). Limited freshwater resources and stringent disposal regulations have provided impetus for FPW reuse. Organic and inorganic compounds released from the shale/brine formation, microbial activity, and residual chemicals added during hydraulic fracturing bestow a unique as well as temporally varying chemical composition to this wastewater. Studies indicate that many of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 110 publications
(167 reference statements)
0
7
0
Order By: Relevance
“…It is difficult to determine the specific mechanism of action of FPW due to its nature as a complex chemical mixture, requiring a variety of instrumentations and techniques that may not be easily accessible. ,, FPW includes salt-forming ions (e.g., Na + , Ca 2+ , and Cl – ), trace metals (e.g., Fe, Zn, Sr, and Ba), and organic compounds (e.g., PAHs and volatile organic compounds). ,, These compounds may contribute to additive, synergistic, or antagonistic toxicity; however, additional studies are required in order to identify the depth of these possibilities. This is further complicated by the new materials made under the conditions in the well-bore environment and every well seemingly has different mixture compounds and concentrations .…”
Section: Resultsmentioning
confidence: 99%
“…It is difficult to determine the specific mechanism of action of FPW due to its nature as a complex chemical mixture, requiring a variety of instrumentations and techniques that may not be easily accessible. ,, FPW includes salt-forming ions (e.g., Na + , Ca 2+ , and Cl – ), trace metals (e.g., Fe, Zn, Sr, and Ba), and organic compounds (e.g., PAHs and volatile organic compounds). ,, These compounds may contribute to additive, synergistic, or antagonistic toxicity; however, additional studies are required in order to identify the depth of these possibilities. This is further complicated by the new materials made under the conditions in the well-bore environment and every well seemingly has different mixture compounds and concentrations .…”
Section: Resultsmentioning
confidence: 99%
“…Although the bacteria grows well in the reactor (as indicated by the high growth rate (Y) value), their low affinity for the substrate causes the COD concentration of effluent to be relatively high [45]. Shwetha et al [46] reported similar conclusions in their literature review on the treatment of WW from unconventional oil and gas extraction processes.…”
Section: Bacterial-based Biological Processesmentioning
confidence: 92%
“…13 Bioreactors exhibited notable efficacy in removing organic matter from low-salinity SGFPW treatment. 55 It was worth studying how to utilize and strengthen the functions of core microorganisms in bioreactors to further improve their organic removal rates and shock load resistance. Besides, there was a lack of anaerobic biotechnology as a result of the slower startup, poor load resistance, and high maintenance costs of anaerobic processes.…”
Section: Eukaryotic Communitymentioning
confidence: 99%